Necesidad de eliminar el numeral 1 del artículo 110 de la ley reformatoria al código civil ecuatoriano - Tacuri Torres, Silvia Rosario (2017)
The legal issues concerning this investigation is aimed at legal analysis of divorce, as it not only has become a legal problem, but primarily social and psychological nature. The Constitution in Article 67 states: "The family is recognized in its various forms. The State shall protect the fundamental nucleus of society and shall guarantee conditions that promote the achievement of its objectives. These may be established by legal or factual bonds and are based on equal rights and opportunities for its members. Marriage is the union between man and woman, it was based on the free consent of the contracting persons and equality of rights, obligations and legal capacity. " For its part, the civil law of Ecuador determined between one of the reasons why marriage can end, specifically the causal first and that is the subject of our study notes: The adultery of one spouse. Adultery as grounds for divorce is a really interesting issue because it involves the study of different areas such as psychology, sociology, religion, among others, in this research try to do display the definitions of each of the historical, legal and behavioral, why and what are the possible causes that lead human beings to engage in this action and the consequences for the individuals involved and the impact this has on society. Finally I have chosen this topic as for testing of adultery as grounds for divorce must admit the hearsay evidence, given that the direct means of checking that ground is almost impossible, no less certain is that through indirect conviction should aim to show precisely the behavior of the defendant unfaithful spouse as well as the mechanics of adultery, and so the actor has the burden of proving in court the circumstances of time, place and manner in which the events occurred, of which It is to conclude that the culprit had sex with someone other than your spouse, in order to satisfy the legal requirements and the judge can appreciate the misconduct imputed to the defendant; and secondly, to be able to determine if the action was recorded timely, that is to be legally able to establish whether or not there was adultery.